A Fixed Point Theorem of Generalized Weakly Contractive Maps in Orbitally Complete Metric Spaces: G.V.R. Babu, P.D. Sailaja - Team, Support (Thai Journal of Mathematics, 2011)
We prove the existence of fixed points of a generalized weakly contractive map in T- orbitally complete metric spaces. This result generalizes the results of Babu and Alemayehu [1] and Rhoades [2] when the space under consideration is bounded.